A novel compound heterozygous missense mutation in ASNS broadens the spectrum of asparagine synthetase deficiency. Issue 6 (7th April 2020) - Wang, Chun; He, Guiyuan; Ge, Yusong; Li, Runjie; Li, Zhenguo; Lin, Yongzhong
Abstract: Background: Asparagine synthetase deficiency (ASNSD) is a rare pediatric congenital disorder that clinically manifests into severe progressive microcephaly, global developmental delay, spastic quadriplegia, and refractory seizures. ASNSD is caused by inheritable autosomal recessive mutations in the asparagine synthetase ( ASNS ) gene. Methods: We performed whole‐exome sequencing using the patient's peripheral blood, and newly discovered mutations were subsequently verified in the patient's parents via Sanger sequencing. Software‐based bioinformatics analyses (protein sequence conservation analysis, prediction of protein phosphorylation sites, protein structure modeling, and protein stability prediction) were performed to investigate and deduce their downstream effects. Results: In this article, we summarized all the previously reported cases of ASNSD and that of a Chinese girl who was clinically diagnosed with ASNSD, which was later confirmed via genetic testing. Whole‐exome sequencing revealed two compound heterozygous missense mutations within the ASNS (c.368T > C, p.F123S and c.1649G > A, p.R550H). The origin of the two mutations was also verified in the patient's parents via Sanger sequencing. The mutation c.368T > C (p.F123S) was discovered and confirmed to be novel and previously unreported. Using software‐based bioinformatics analyses, we deduced that the two mutation sites are highly conserved across a wide range of species, with the ability to alter different phosphorylation sites and destabilize the ASNS protein structure. The newly identified p.F123S mutation was predicted to be the most significantly destabilizing and detrimental mutation to the ASNS protein structure, compared to all other previously reported mutations. Conclusion: Evidently, the presence of these compound heterozygous mutations could lead to severe clinical phenotypes and serve as a potential indicator for considerably higher risk with less optimistic prognosis in ASNSD patients. Abstract : Asparagine synthetase deficiency (ASNSD) is an extremely rare pediatric congenital disorder with severe progressive microcephaly, severe global developmental delay, spastic quadriplegia, and refractory seizures as the main clinical manifestations. Mutations in asparagine synthetase (ASNS) are considered the primary culprits for ASNSD patients. Our study here has expended the current mutations spectrum and database for human ASNS with the newly identified mutation p.F123S as not only a potential risk factor for more severe phenotypes, but also a prognosis for ASNSD patients.